Automatic tissue classification in magnetic resonance brain images via combined methods - Sepideh Yazdani, 1980-, author; Rubiyah Yusof, supervisor; Institut Teknologi Antarabangsa Malaysia-Jepun (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2016